Eficacia de la terapia antiangiogénica sobre las membranas neovasculares retinales (2021)
The objective of this research is to establish the effectiveness of antiangiogenic drugs for the treatment of the neovascular membrane produced in high myopia, and exudative AMD; used at the Neiva Oftalmolaser Clinic between 2013 and 2020. The research is retrospective. For data collection, a review of information was carried out, of ophthalmological medical records from the years 2013 to 2020 of the Oftalmolaser Clinic of the city of Neiva and results were found regarding the recovery or stabilization of visual acuity and the combination of antiangiogenic drugs during treatment; concluding that the most used drug is Ranibizumab and that the total number of eyes that improved was 45.2%.